Anomaly induced inflation in the minimal quartic extension of Einstein’s gravity - Kerim Demirel; Bayram Tekin (European Physical Journal C: Particles and Fields)
Abstract A particular extension of Einstein’s General Relativity up to and including quartic terms in the curvature tensor is minimal in the sense that it has a unique maximally symmetric vacuum and only a massless spin-2 excitation in its spectrum around the vacuum. We study the inflation phase of the universe in this minimal quartic extension of Einstein’s gravity in the presence of trace anomaly terms coming from the Standard Model fields and the fields of the Minimal Supersymmetric Standard Model. We show that the theory allows a quasi-de Sitter phase with sufficient e-foldings.